(3cJGH GdYQhVs - (3GHf GdSbGW , CHh YHO Gddgs
(3ChdgG (B:s
(3GdTYQ eQcH ef SHH hhJO haGUdI aGdSHH VQHGf Naja hKbjd aGdNaja eJMQc hSGcf hGdKbjd eJMQcGf s
(3BNQgG (B:s
(3hbhdi SjOi gGQhf HGdYgO GdPi cfG YgOfG ade jZdg ced HMeO Gddg hGdUdGI hGdSdGe Ydi ehdGfG eMeO QShd Gddg Udi Gddg Ydjg hSde JSdjekG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B3s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B6s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1438s
(3eUOQ GbJfGA GdCUd (B:s
(3ESchQjGd (B(288/3) s
Keywords: (3GdYQhV hGdbhGais